Penguatan Program Pengabdian Masyarakat Melalui Kegiatan KKL Posdaya Masjid - Fattah, Mustamin; Sayuri, Sayuri (LP2M IAIN Samarinda, 2019)
This research is based on the phenomenon that community service activities carried out by Perguruan Tinggi Agama Islam (PTAI) from more or less the same year have not been linked to the results of research in the social religious field. As a result, the relevance, benefits, and contribution of PTAI to the community become less visible. This research is a field work research. Partisipatory Action Reseacrh analysis was used in this study. The results of this study are 1) Strategy to build public awareness about clean living in the environment is done by inviting them to work together to clean the environment starting from cleaning the mosque, TPA, Mushalla, and educational institutions around. 2) Strategies to develop a community mindset can realize the potential of nature and the surrounding human resources to be processed through socialization on the use of the natural environment, including household waste, training in making paving blocks from plastic waste, and processing waste into compost. 3) Strategy to build active communication between citizens and the government with assistance to citizens, and 4) Strategy to build a spirit of diversity in the community.